Practical implementation of differentiated approach to developing water aerobics classes for early adulthood women with different types of body build - Kolos, Mykola Anatoliiovych; Tkachova, Anna; Dutchak, Myroslav; Kashuba, Vitalii Oleksandrovych; Goncharova, Nataliia; Lytvynenko, Yurii; Vako, Illia; Lopatskyi, Serhii (Journal of Physical Education and Sport, 2020)
Practical implementation of differentiated approach to developing water aerobics classes for early adulthood women with different types of body build. The purpose of the article is to establish effectiveness of influence of Water Aerobics classes for early adulthood women with different types of body build on their physical development indices. Results. The approach to building-up health fitness classes which is based on differentiation of exercise workload in accordance with the type of body build of early adulthood women (asthenic, normosthenic, hypersthenic) was developed. The dynamics of physical development indices in early adulthood women under the influence of Water Aerobics classes in accordance with their body build type was studied. The research involved 46 women of the above-mentioned category, with 73,9 % of normosthenic type, 15,2 % of asthenic one and 10,9 % of hypersthenic one. It was proved that women who took the developed exercise program experienced normalization of body length-weight ratio, the number of women with average level of body type balance increased, optimization of fat and muscle components of their bodies took place. Women of asthenic body type experienced optimization of their weight, the ones of normosthenic type had redistribution of body fat and muscle components with increase of muscle component by means of fat component decrease, women of hypersthenic type demonstrated improvement of all physical development indices under research. The conducted research contributed to corpus of data regarding the increase of effectiveness of Water Aerobics classes for early adulthood women with different types of body build.

Практична реалізація диференційованого підходу до розвитку занять аквааеробікою для жінок раннього віку з різними типами статури. Мета статті – встановити ефективність впливу занять аквааеробікою для жінок раннього віку з різними типами статури на показники їх фізичного розвитку. Результати. Розроблено підхід до проведення відновлюючих оздоровчих занять фітнесом, який базується на диференціації фізичного навантаження відповідно до типу будови тіла жінок раннього дорослого віку (астенік, нормостенік, гіперстенік). Досліджено динаміку показників фізичного розвитку жінок раннього зрілого віку під впливом занять аквааеробікою відповідно до типу статури. У дослідженні взяли участь 46 жінок вищевказаної категорії, з них 73,9 % нормостенічного типу, 15,2 % астенічного та 10,9 % гіперстенічного. Доведено, що у жінок, які виконували розроблену програму вправ, відбулася нормалізація співвідношення довжини та маси тіла, збільшилася кількість жінок із середнім рівнем балансу типів статури, відбулася оптимізація жирової та м’язової складових тіла. У жінок астенічного типу статури відбулася оптимізація маси тіла, у жінок нормостенічного типу відбувся перерозподіл жирової та м’язової складової тіла зі збільшенням м’язової складової за рахунок зменшення жирової, у жінок гіперстенічного типу відмічено покращення всіх досліджуваних показників фізичного розвитку. Проведене дослідження сприяло отриманню масиву даних щодо підвищення ефективності занять аквааеробікою для жінок раннього дорослого віку з різними типами статури.
Keywords: women; Water Aerobics; development; distribution; influence; effectiveness; жінки; аквааеробіка; розвиток; поширення; вплив; ефективність